Progress in scale modeling. selections from the International Symposia on Scale Modeling, ISSM VI (2009) and ISSM VII (2013) /: selections from the International Symposia on Scale Modeling, ISSM VI (2009) and ISSM VII (2013). Volume II : ([2015]) - Unknown
No abstract available